The Effects of Proper Inventory Management on the Profitability of SMEs - Sah, Genesis Gyasi; Füredi-Fülöp, Judit (Technium Social Sciences Journal, 2022)
A business must have or be able to generate enough cash and cash equivalent to meet its short-term liabilities if it is to continue and grow in business. Therefore, working capital management which helps an entity to, efficiently and effectively control current assets and liabilities is a key factor in the company’s long-term success; without working capital, the non- current assets will not function. The greater the extent to which current assets exceed current liability, the more solvent or liquid a company is likely to be. This paper observes the relationship between working capital management practices of small and medium enterprises (SMEs) and the performance and profitability of these businesses in the Kumasi Metropolis , to evaluate inflows and outflows of inventory to determine the rate at which certain goods are purchased in relation to others. This practice will also help ascertain seasons and times during which certain products experience higher demand and vice versa. This will reduce their over and/or under investment in inventories. The implication of the findings is that the government of Ghana should pursue policies aimed at encouraging training and improving the managerial skills of SME owner/managers as well as creating the enabling environment for the development of improved modern technologies to transform the business processes of these vital industries.